THE POLYNOMIALS AND THEIR CONGRUENCE - Fazyl, Z. G.; Alimbaev, А.А. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2020)
Polynomials play an important role in mathematics, in programming, in applied physics, and in many sciences. It has not been fully studied as a branch of algebra, and there are many questions regarding this section. In this scientific article I tried to explain in simple words the concept of a “polynomial” and what properties it possesses, as well as what actions and operations we can perform with them.
Keywords: the polynomials ring; congruence; polynomial addition; polynomial multiplication; modulo